Biocimentação em solo argiloso residual de basalto - Callai, Nicole Deckmann (2021)
Biotechnological processes have been gaining prominence in civil construction, especially at a time when alternative and sustainable materials and/or techniques are being sought to supplement the growing demand for urban infrastructure. Biocementation is a microbiological process of calcium carbonate precipitation used to improve the soil properties, such as increased compressive strength and reduced permeability of sandy soils, but still finds many limitations on application in fine-grained soils. Based on that, the objective of this work is to evaluate the efficiency of biocementation in a basalt clayey oxisol, analyzing the influence of the application method of the feed solution on the calcite precipitation and its consequent mechanical response. For that, undisturbed cylindrical soil samples of 5,3cm in diameter and 8cm in height were extracted, subsequently subjected to percolation/injection of the biocementing solution, and a simple compression test was performed to analyze the influence of the application method on the biocementation efficiency. X-ray diffraction (XRD), X-ray fluorescence (XRF) and infrared spectroscopy (FTIR) tests were also performed to assess the calcite occurrence and distribution across the samples. Based on test results that have analyzed the influence of the void index and molding humidity on calcite precipitation, it was decided to use undisturbed samples since none of the factors analyzed have had a significant influence on the specimens biocementation. The results of the simple compression test were not statistically different for the biocemented and non-biocemented samples, with the percolated specimens showing 38,24kPa of average resistance, the injected specimens showing 33,80kPa and the white specimens, 29,01kPa, all of them with high standard deviations due to the great data variability. The compressive strength results were attributed to the sample void indices, which showed some discrepancy due the soil heterogeneity. A Pearson correlation of -0,54 was observed between void index and compressive strength, indicating an inverse dependence. Diffraction and fluorescence proved the existence of a greater calcium carbonate amount in the sample upper third compared to the middle and lower thirds, indicating the biocementation efficiency decreases with increasing depth. The FTIR test has been characterized mineralogically the samples, showing the calcium carbonate existence in the biocemented ones. Finally, it is concluded that neither percolation or injection were efficient methods to improve the soil mechanical behavior, because they provide biocementation occurrence, but not in sufficient quantity or even in uniform distribution among the samples.